Motivasi Petani dalam Usahatani Padi di Kecamatan Singkawang Utara Kota Singkawang - Wardhana, Restu Dwi; Kusrini, Novira; Hutajulu, Josua Parulian (Universitas Galuh, 2025)
This study aims to analyze the factors influencing farmers' motivation in rice farming in Singkawang Utara Subdistrict, Singkawang City. The approach used is quantitative, with primary data collected through structured interviews and questionnaires. The analysis applies Alderfer's (1969) ERG (Existence, Relatedness, Growth) theory. The results show that land size has a positive but insignificant relationship with farmers' motivation in the social relationship (Relatedness) dimension, while land ownership status and farm income have no significant impact on other motivational dimensions. These findings indicate that although land ownership provides economic security, it is insufficient to enhance farmers' innovation and self-development. Non-economic support, such as training and access to technology, is necessary to improve farmers' motivation.key in increasing the production and usefulness of aloe vera farming in North Pontianak District.